Branching out: Towards a trait-based understanding of fungal ecology. Issue 1 (May 2015) - Aguilar-Trigueros, Carlos A.; Hempel, Stefan; Powell, Jeff R.; Anderson, Ian C.; Antonovics, Janis; Bergmann, Joana; Cavagnaro, Timothy R.; Chen, Baodong; Hart, Miranda M.; Klironomos, John; Petermann, Jana S.; Verbruggen, Erik; et al.
Abstract Fungal ecology lags behind in the use of traits (i.e. phenotypic characteristics) to understand ecological phenomena. We argue that this is a missed opportunity and that the selection and systematic collection of trait data throughout the fungal kingdom will reap major benefits in ecological and evolutionary understanding of fungi. To develop our argument, we first employ plant trait examples to show the power of trait-based approaches in understanding ecological phenomena such as identifying species allocation resources patterns, inferring community assembly and understanding diversity–ecosystem functioning relationships. Second, we discuss ecologically relevant traits in fungi that could be used to answer such ecological phenomena and can be measured on a large proportion of the fungal kingdom. Third, we identify major challenges and opportunities for widespread, coordinated collection and sharing of fungal trait data. The view that we propose has the potential to allow mycologists to contribute considerably more influential studies in the area of fungal ecology and evolution, as has been demonstrated by comparable earlier efforts by plant ecologists. This represents a change of paradigm, from community profiling efforts through massive sequencing tools, to a more mechanistic understanding of fungal ecology.